Elementary teachers’s readiness to implement online learning during the covid-19 pandemic - Dindin Abdul Muiz Lidinillah; Babang Robandi; Wahyudin Wahyudin; Dianasari Dianasari (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2021)
This study reveals the experience and readiness of elementary teachers to carry out online learning during the COVID-19 pandemic. Readiness includes technological, technical, and pedagogical readiness. Internet survey research has been conducted on 203 teachers consisting of 50 male teachers and 153 female teachers. The research instrument consists of two parts. The first part consists of 14 items of teacher teaching experience during the pandemic, one item about the obstacles experienced by teachers, 10 items about the devices used by teachers during the pandemic. The second part consists of 30 items on the technological readiness: technical (17 items) and pedagogical (13 items) of teachers to carry out online learning. The results of the study describe various experiences, obstacles, and the use of various devices in carrying out learning during the pandemic. Technological, technical, and pedagogical readiness of teachers tends to be high where the age of the teacher is significantly correlated with teacher readiness. Another finding is that gender is not a significant factor in teacher readiness.